Guerre et amour dans L’Amour au temps du choléra de Gabriel García Marquez et L’Amour aux temps des scélérats d’ Anouar Benmalek - ZERROUK AHLEM (My University, 2023)
Abstract Our study deals with the themes of love and war in The love in the time of cholera by Gabriel Garcia Marquez and The love in the times of scoundrels by Anouar Benmalek. It aims to examine the degree of intertextuality in Anouar Benmalek and the textual rapprochement inherent in the writing of these two themes
Keywords: Keywords Intertexuality, love, war, political commitment